Biomagnification of Mercury Through the Aquatic Food Chain in Lake Lebo Taliwang West Sumbawa - Rahman, Abdul; Maria Ulfa, Andi; Junaidi efendi; Supriastuti, Eko (Jurnal Biologi Tropis, 2025)
Lebo Taliwang Lake has been reported to be polluted by mercury compounds. This study aims to determine the occurrence of mercury biomagnification in the food chain in Lebo Lake Taliwang. Samples of water, tilapia, water strider and japan pond heron were taken at two sampling locations: inlet and outlet. Samples were tested for mercury content with a mercury analyzer. The results show that there is mercury accumulation in the Lebo Taliwang Lake ecosystem. The average of each sample was 1.95 in water, 99.5 in tilapia, 79.8 in water srider, and 948.09 and 143 in feathers and blood, respectively. Furthermore, the results of the biomagnification factor (BMF) value show the BMF>1. This means that there is biomagnification of mercury in Lebo Taliwang Lake. The biomagnification value of japan pond heron in feather and blood with nile tilapia is 9.52 and 1.43. Meanwhile, with water stider, the values are 11.87 and 1.81. This study recommends enhanced monitoring and regulation of illegal gold mining (PETI) activities, as well as environmental rehabilitation efforts around Lake Lebo